Investigating associations between maternal stress, smoking and adverse birth outcomes: evidence from the All Our Families cohort - Shelby S. Yamamoto; Shahirose S. Premji; Vineet Saini; Sheila W. McDonald; Gian S. Jhangri (BMC, 2023)
Abstract Background Independently, active maternal and environmental tobacco smoke exposure and maternal stress have been linked to an increased risk of preterm birth and low birth weight. An understudied relationship is the potential for interactive effects between these risk factors. Methods Data was obtained from the All Our Families cohort, a study of 3,388 pregnant women < 25 weeks gestation recruited from those receiving prenatal care in Calgary, Canada between May 2008 and December 2010. We investigated the joint effects of active maternal smoking, total smoke exposure (active maternal smoking plus environmental tobacco smoke) and prenatal stress (Perceived Stress Scale, Spielberger State-Trait Anxiety Inventory), measured at two time points (< 25 weeks and 34-36 weeks gestation), on preterm birth and low birth weight. Results A marginally significant association was observed with the interaction active maternal smoking and Spielberger State-Trait Anxiety Inventory scores in relation to low birth weight, after imputation (aOR = 1.02, 95%CI: 1.00-1.03, p = 0.06). No significant joint effects of maternal stress and either active maternal smoking or total smoke exposure with preterm birth were observed. Active maternal smoking, total smoke exposure, Perceived Stress Scores, and Spielberger State-Trait Anxiety Inventory scores were independently associated with preterm birth and/or low birth weight. Conclusions Findings indicate the role of independent effects of smoking and stress in terms of preterm birth and low birthweight. However, the etiology of preterm birth and low birth weight is complex and multifactorial. Further investigations of potential interactive effects may be useful in helping to identify women experiencing vulnerability and inform the development of targeted interventions.